The Specifically Androgen-Regulated Gene (SARG) Promotes Papillary Thyroid Carcinoma (PTC) Lymphatic Metastasis Through Vascular Endothelial Growth Factor C (VEGF-C) and VEGF Receptor 3 (VEGFR-3) Axis - Xu, Shuai-Jun; Jin, Bin; Zhao, Wei-Jun; Chen, Xue-Xian; Tong, Ying-Ying; Ding, Xiao-Fei; Chen, Ying-Yuan; Wang, Dong-Hao; Wang, Zhi-Ming; Dai, Bing-Qing; Chen, Sai; Liang, Yong; et al. (Frontiers in Oncology, 2022)
The papillary thyroid carcinoma (PTC) metastasizes through lymphatic spread, but the follicular thyroid cancer (FTC) metastasis occurs by following hematogenous spread. To date, the molecular mechanism underlying different metastatic routes between PTC and FTC is still unclear. Here, we showed that specifically androgen-regulated gene (SARG) was significantly up-regulated in PTC, while obviously down-regulated in FTC through analyzing Gene Expression Omnibus (GEO) database. Immunohistochemistry assay verified that the PTC lymph node metastasis was associated with higher levels of SARG protein in clinical PTC patient samples. SARG-knockdown decreased TPC-1 and CGTH-W3 cells viability and migration significantly. On the contrary, SARG-overexpressed PTC cells possessed more aggressive migratory ability and viability. In vivo, SARG overexpression dramatically promoted popliteal lymph node metastasis of xenografts from TPC-1 cells mouse footpad transplanting. Mechanistically, SARG overexpression and knockdown significantly increased and decreased the expression of vascular endothelial growth factor C (VEGF-C) and VEGF receptor 3 (VEGFR-3) respectively, thereby facilitating or inhibiting the tube formation in HUVECs. The tube formation experiment showed that SARG overexpression and knockdown promoted or inhibited the number of tube formation in HUVEC cells, respectively. Taken together, we showed for the first time the differential expression profile of SARG between PTC and FTC, and SARG promotes PTC lymphatic metastasis via VEGF-C/VEGFR-3 signal. It indicates that SARG may represent a target for clinical intervention in lymphatic metastasis of PTC.